A Morphometeric Study of the Effects of Ibuprofen on the Stomach of Albino Rats under Light Microscope (Medical Forum Monthly, 2024)
Objective: To observe the effects of ibuprofen on the stomach of the albino rats under light microscope and its morphometeric analysis.Study Design: A prospective experimental study.Place and Duration of Study: This study was conducted at the Department of Anatomy, Basic Medical Sciences Institute, Jinnah Postgraduate Medical Centre Karachi during 01.04.2008 to 31.05.2008.Materials and Methods: Thirty male adult albino rats were taken for the study and were divided into two groups containing 15 animals each. Each group was divided in to three sub groups according to the time of sacrifice i.e. 4,6 and 8 weeks. Group A served as control. Group B received ibuprofen at the dose of 70 mg per kilogram body weight per day orally with feed. After completion of respective period of treatment animals were sacrificed, abdomen was opened. The stomach was removed and opened along the greater curvature, divided into cardiac, body and pyloric parts and was fixed in Buffered neutral formalin for 24 hours. After that tissues were processed in ascending strength of alcohol, cleared in xylene and infiltrated and embedded with paraffin. Five micron thick sections were made on the rotatory microtome, were stained with Haematoxylin and eosin (for general morphology and morphometric study), and with Periodic Acid Schiff Orange-G (for the mucus content of the surface mucus cells and the mucus neck cells), randomly selected every seventh stained section, in three fields were studied.Results: In stained sections of all parts of stomach the lining epithelium was disrupted, exfoliated, and ulcers and erosions were present. The erosive areas contained red blood cells and extended deep in to lamina propria. The results of mucosal thickness and the mean values of number of surface mucous cell count was moderately significant (P < 0.001) to highly significant ((P < 0.0001) in all parts of stomach when compared to control. The mucous content of the surface mucous cell in subgroups ‘B’1, ‘B’2 and ‘B’3 of cardiac and pyloric parts were same marked (++++), while in body part of stomach it was moderate (+++) same as in control animals respectively.Conclusion: Based on present study, it is concluded that Ibuprofen induces gastric mucosal damage.